How much does the warm-up contribute to the soccer match-day load? - Williams, J. H.; Jaskowak, D. J.; Williams, M. H. (Sport Performance & Science Reports, 2019)
During competitive soccer matches, collegiate females cover approximately 10km of total distance (5, 6, 9, 10). We and others have found that they exercise at about 80% of maximal heart rate and expend nearly 50 kJ of energy per kg body mass (4, 10). Prior to each match, teams conduct a pre-match warm up that includes both physical activities and technical skills. Unfortunately, data concerning the physiological demands of the warm-up are scarce. This is unfortunate since this period of activity likely contributes to the overall workload during the session.